Therapeutic efficacy of liraglutide versus metformin in modulating the gut microbiota for treating type 2 diabetes mellitus complicated with nonalcoholic fatty liver disease - Ying, Xing; Rongjiong, Zheng; Kahaer, Mayila; Chunhui, Jiang; Wulasihan, Muhuyati (Frontiers in Microbiology, 2023)
Metformin and liraglutide are used in the treatment of type 2 diabetes mellitus (T2DM) complicated with nonalcoholic fatty liver disease (NAFLD). Although these drugs can alter the intestinal microbiome, clinical data are required to explore their mechanisms of action. Using 16S sequencing technology, we analyzed and compared the intestinal bacterial community structure and function between patients before and after treatment (12 weeks) with the two drugs (metformin or liraglutide, n = 15) and healthy controls (n = 15). Moreover, combined with 19 clinical indices, the potential therapeutic mechanisms of the two drugs were compared. The studied clinical indices included those associated with islet β-cell function (FPG, FINS, HbA1c, and HOMA-IR), inflammation (TNF-α, IL-6, and APN), lipid metabolism (TC, TG, and LDL-C), and liver function (ALT, AST, and GGT); the values of all indices changed significantly after treatment (p < 0.01). In addition, the effect of the two drugs on the intestinal bacterial community varied. Liraglutide treatment significantly increased the diversity and richness of the intestinal bacterial community (p < 0.05); it significantly increased the relative abundances of Bacteroidetes, Proteobacteria, and Bacilli, whereas metformin treatment significantly increased the relative abundance of Fusobacteria and Actinobacteria (p < 0.05). Metformin treatment increased the complexity and stability of the intestinal bacterial network. However, liraglutide treatment had a weaker effect on the intestinal bacterial network, and the network after treatment was similar to that in healthy controls. Correlation matrix analysis between dominant genera and clinical indicators showed that the correlation between the bacterial community and islet β-cell function was stronger after liraglutide treatment, whereas the correlation between the bacterial community and inflammation-related factors was stronger after metformin treatment. Functional prediction showed that liraglutide could significantly affect the abundance of functional genes related to T2DM and NAFLD (p < 0.05), but the effect of metformin was not significant. This study is the first to report the changes in the intestinal bacterial community in patients treated with metformin or liraglutide and the differences between the mechanisms of action of metformin and liraglutide. Metformin or liraglutide has a therapeutic value in T2DM complicated with NAFLD, with liraglutide having a weaker effect on the intestinal bacterial community but a better therapeutic efficacy.